2021
DOI: 10.1108/imds-08-2020-0484
|View full text |Cite
|
Sign up to set email alerts
|

Beauty matters: reducing bounce rate by aesthetics of experience product portal page

Abstract: PurposeThis study aims to investigate the impact of experience product portal page aesthetics on bounce rate.Design/methodology/approachThis research collected data from an online shop selling original design furniture on Taobao.com. It employed deep learning algorithm and manual coding to operationalize image and text aesthetics.FindingsThe empirical results indicate that text aesthetics has a U-shaped relationship with bounce rate, whereas the relationship between image aesthetics and bounce rate is insignif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 95 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…For instance, we found a strong correlation between bounce rates and exit rates. This suggested that bounce rates could be influenced by factors not included in our dataset, such as the visual aesthetics of the website [ 48 ] or general trust in e-commerce platforms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we found a strong correlation between bounce rates and exit rates. This suggested that bounce rates could be influenced by factors not included in our dataset, such as the visual aesthetics of the website [ 48 ] or general trust in e-commerce platforms.…”
Section: Discussionmentioning
confidence: 99%
“…However, a product's visual aesthetic does not always yield positive results. For instance, Wang et al . (2021) found no significant direct effect between a product image's aesthetic and the bounce rate, a measure of customer engagement in e-commerce.…”
Section: Hypotheses Developmentmentioning
confidence: 99%